Insights of HBV Pathogenesis and Emerging Clinical Therapies for HBV Induced HCC Patients for a Better Prognostic Outcome - Chatterjee, Reshmi; Mitra, Abhisek (Asian Journal of Medical Sciences, 2015)
Chronic hepatitis B (CHB) virus infection is a global epidemic and a major cause of hepatocellular carcinoma (HCC). Approximately, 400 million people with 1.5 million Americans are chronically infected with this virus and around 1 million deaths from HBV annually have been estimated. High serum viral load has been detected between 75-80% of HCC patients. Epidemiological studies revealed that there are geographical variations in the incidence rate of hepatitis B virus genotype and subgenotypes. Furthermore, HBV induced HCC has a direct correlation with the recurrent genomic integration of this virus and cross-talk of its oncogenic protein HBV x (HBx) with different cellular signaling pathways. With the help of an extensive pathological study, whole genome sequencing and molecular insights of HBV induced HCC patients, suitable medications providing high-genetic barrier to resistances are made available. These medications can prevent HCC by inhibiting viral replication, modulating the immune response or both. The evolution of drugs with superior efficacy and less toxicity are providing important tools for clinicians to reduce HBV related HCC. This review sheds new perspective on molecular insight of HBV life cycle and clinical updates to treat sustained virus infection and associated cancers. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11884 Asian Journal of Medical Sciences Vol.6(4) 2015 1-8